Changing pattern of alcoholic liver disease in Great Britain: relation to sex and signs of autoimmunity. Issue 6075 (11th June 1977) - Krasner, N; Davis, M; Portmann, B; Williams, R
Abstract : A survey of 293 patients with alcoholic liver disease showed that women, particularly those aged under 45, had a significantly higher incidence of alcoholic hepatitis, with or without superimposed cirrhosis, than men. The long-term prognosis for both women who continued to drink and those who stopped drinking was worse than that for men. Autoantibodies were more common in women, which suggested that immune mechanisms may play a part in the pathogenesis and progression of alcoholic liver disease in women.